Increased foot-stretcher height improves rowing performance: evidence from biomechanical perspectives on water. Issue 2 (3rd March 2020) - Liu, Yang; Gao, Binghong; Li, Jiru; Ma, Zuchang; Sun, Yining
Abstract: The aim of this study was to investigate whether changes on foot-stretcher height were associated with characteristics of better rowing performance. Ten male rowers performed a 200 m rowing trial at their racing rate at each of three foot-stretcher heights. A single scull was equipped with an accelerometer to collect boat acceleration, an impeller with embedded magnets to collect boat speed, specially designed gate sensors to collect gate force and angle, and a compact string potentiometer to collect leg drive length. All sensor signals were sampled at 50 Hz. A one-way repeated measures ANOVA showed that raising foot-stretcher position had a significant reduction on total gate angle and leg drive length. However, a raised foot-stretcher position had a deeper negative peak of boat acceleration at the catch, a lower boat fluctuation, a faster leg drive speed, a larger gate force for the port and starboard side separately. This could be attributed to the optimisation of the magnitude and direction of the foot force with a raised foot-stretcher position. Although there was a significant negative influence of a raised foot-stretcher position on two kinematic variables, biomechanical evidence suggested that a raised foot-stretcher position could contribute to the improvement of rowing performance.